Autobiographical Memory and Psychological Distress in a Sample of Upper-Limb Amputees - Luchetti, Martina (Public Library of Science, 2014)
Amputation is a traumatic and life-changing event that can take years to adjust to. The present study (a) examines psychological adjustment in a specific trauma-exposed sample, (b) compares the phenomenology (e.g., vividness) of amputation-related memories to more recent memories, and (c) tests whether memory phenomenology is associated with psychological distress. A total of 24 upper-limb amputees recalled two autobiographical memories–an amputation-related memory and a recent memory–and rated the phenomenological qualities of each memory, including Vividness, Coherence, Emotional Intensity, Visual Perspective, and Distancing. Participants also completed self-rated measures of psychological distress and personality. The sample was generally well adjusted; participants showed no relevant symptoms of anxiety and depression, and personality scores were similar to the general population. There were no significant differences in phenomenology between the two types of memories recalled. Even though amputation-related memories were, on average, almost 20 years older than the recent memories, they retained their intense phenomenology. Despite the intensity of the memory, none of the phenomenological dimensions were associated with psychological distress. It is worth to further define which dimensions of phenomenology characterize memories of traumatic events, and their association with individuals' psychological reactions.